Potensi Kulit Jeruk Bali (Citrus Maxima Merr) Sebagai Antibakteri Propionibacterium acne Penyebab Jerawat - JOHAN AXEL PARIURY; JUAN PAUL CHRISTIAN HERMAN; TIFFANY REBECCA; ELVINA VERONICA; I GUSTI KAMASAN NYOMAN ARIJANA (Universitas Hang Tuah, 2021)
Introduction: Acne or known as acne vulgaris is an inflammation of the pilosebaceous layer with blockage of the keratin material due to the Propionibacterium acnes (P.acne) bacteria. The prevalence of acne in Indonesia is 80%-85% in adolescents. Acne appearances can cause insecurity in our look. Acne medication has irritation side effects and already resistant so other alternatives medicines are needed. The production of pomelo (Citrus maxima merr) in Indonesia reaches 511 kg annually with a weight of 208 kg of pomelo peel. About 50% of pomelo peel is removed without reprocessing even though it contains a lot of antioxidants and antibacterial properties. Aims: To know the potential of pomelo peel as an alternative antibacterial P.acne that causes acne. Methods: Literature study using research articles or literature review articles from international and national journals in 10 years. Accessed from Pubmed, Garuda, NCBI, and Google Scholar by typing keywords. Around 30 articles were used in this review article. Results: The antioxidants of pomelo peel interfere with metabolism by inhibiting the performance of the enzyme reversing RNA transcriptase, DNA topoisomerase, transporting active bacteria, disrupting PH regulation, denaturing bacterial proteins, damaging cell membranes thus inhibiting replication and causing the death of P.acne. Conclusion: Pomelo peel is considered to be an antibacterial P.acne that causes acne. Further research is needed, especially in extract concentrations and side effects.